ChemInform Abstract: A New Family of Lanthanide Borate Halides with Unusual Coordination and a New Neodymium‐Containing Cationic Framework. Issue 20 (25th April 2013) - Polinski, Matthew J.; Alekseev, Evgeny V.; Darling, Victoria R.; Cross, Justin N.; Depmeier, Wulf; Albrecht‐Schmitt, Thomas E.
Abstract La[B7O10(OH)3(H2O)Br] (I), Ln[B6O9(OH)2(H2O)2Br] ·0.5H2O (II) (Ln: Ce, Pr), Nd2 [B12O17.5(OH)5 (H2O)4Br1.5] Br0.5·H2O (III), Sm4[B18O25(OH)13Br3] (IV), and Ln[B7O11(OH)(H2O)I] (V) (Ln: La, Ce, Pr, Nd, Sm) are synthesized from the respective lanthanide oxides, H3BO3, and HBr or HI (autoclave, 200—240 °C, 5—7 d, 60—85% yields).